Time Evolution of Meteorological Training and Education in India (MAUSAM, 2025)
An attempt has been made to trace out the time evolution of training services of India Meteorological Department in the disciplines of General Meteorology, Agricultural Meteorology, and Meteorological instruments & telecommunication through its two World Meteorological Organization Regional Training Centre (WMO RTC) components. The success of the training courses which are organized by these RTCs in the framework of Guidelines for the Education and Training of Personnel in Meteorology and Operational Hydrology (WMO- No. 258) has been widely recognized by the national and international stakeholders as well as the WMO and other related international organizations. The design of the training syllabi fulfils the competency requirements, set by WMO & ICAO. Some new training courses which reflect the advances in meteorology and hydrology have also been offered to enhance the capabilities of trainees in the use of the up-to-date numerical products. In addition to face-to-face teaching, blended learning has been introduced for some training courses to enhance the training efficiency.